Web-based e-journal service quality and satisfaction in research and non-research universities - Mohd Zain, Wahidah; Othman, Roslina (IIUM Press, International Islamic University Malaysia, 2017)
Malaysian public universities can be categorized into Research (RU) and NonResearch Universities (Non-RU). Both types of universities are distinct in many aspects such as budget allocation, research productivity, and management process. Web-based e-journal service is crucial for library users in RU and Non-RU alike especially for those who conduct research. Therefore, users’ satisfaction is considered the key to keep users loyal to the service. Thus, users’ perception of the service quality needs to be continuously examined andto hit excellent level as it reflects users’ satisfaction. Unfortunately, many studies especially in Non-RU showed that users’ satisfaction level of library e-service or web-based service was only moderate. In fact, no study has clearly compared between RU and Non-RU focusing on web-based ejournal service quality and users’ satisfaction. Thus, this book is conducted to fill the gap with four main objectives: